# |
ODE |
Mathematica |
Maple |
\[
{}x \left ({y^{\prime }}^{2}-1\right ) = 2 y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (1-y^{2}\right ) {y^{\prime }}^{2} = 1
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}+\left (x y-1\right ) y^{\prime } = y
\] |
✗ |
✗ |
|
\[
{}y^{2} {y^{\prime }}^{2}+x y y^{\prime }-2 x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}-2 x y y^{\prime }+2 y^{2} = x^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+\left (x +y-2 x y\right ) {y^{\prime }}^{2}-2 y^{\prime } x y \left (x +y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+\left (y^{2}-x^{3}-x y^{2}\right ) y^{\prime }-x y \left (x^{2}+y^{2}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y = y^{\prime } x \left (y^{\prime }+1\right )
\] |
✓ |
✓ |
|
\[
{}y = x +3 \ln \left (y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}y \left (1+{y^{\prime }}^{2}\right ) = 2
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}-2 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+y^{2} = 1
\] |
✓ |
✓ |
|
\[
{}x \left ({y^{\prime }}^{2}-1\right ) = 2 y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}4 x -2 y y^{\prime }+x {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y+{y^{\prime }}^{2} = x^{3} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2} = 3 x y^{\prime }+y
\] |
✓ |
✓ |
|
\[
{}8 x +1 = y {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+2 y^{\prime }+1 = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+{y^{\prime }}^{2}\right ) x = \left (x +y\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x^{2}-3 y y^{\prime }+x {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y+2 x y^{\prime } = x {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x = {y^{\prime }}^{2}+y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x = y-{y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}x +2 y y^{\prime } = x {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}4 x -2 y y^{\prime }+x {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{3} = y y^{\prime }+1
\] |
✓ |
✓ |
|
\[
{}y \left (1+{y^{\prime }}^{2}\right ) = 2 x y^{\prime }
\] |
✓ |
✓ |
|
\[
{}2 x +x {y^{\prime }}^{2} = 2 y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x = y y^{\prime }+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}4 x {y^{\prime }}^{2}+2 x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y = y^{\prime } x \left (y^{\prime }+1\right )
\] |
✓ |
✓ |
|
\[
{}2 x {y^{\prime }}^{3}+1 = y {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+x y y^{\prime } = 2 y^{2}
\] |
✓ |
✓ |
|
\[
{}3 {y^{\prime }}^{4} x = {y^{\prime }}^{3} y+1
\] |
✗ |
✓ |
|
\[
{}2 {y^{\prime }}^{5}+2 x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}\frac {1}{{y^{\prime }}^{2}}+x y^{\prime } = 2 y
\] |
✓ |
✓ |
|
\[
{}2 y = 3 x y^{\prime }+4+2 \ln \left (y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\frac {1}{y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }-\sqrt {y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\ln \left (y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\frac {3}{{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }-{y^{\prime }}^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+{\mathrm e}^{y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}\left (-x y^{\prime }+y\right )^{2} = 1+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-y y^{\prime }-2 = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}-2 x y y^{\prime }+{y^{\prime }}^{2} \left (x^{2}-1\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 \,{\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2}{\sqrt {-x^{2}+1}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \arcsin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2} y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -x \,{\mathrm e}^{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \sin \left (y\right ) = x^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-3 y^{\prime }+2 = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t^{2}+3
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t \,{\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (t \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {t}{t^{2}+4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \ln \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {t}{\sqrt {t}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y-4
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {{\mathrm e}^{t}}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t \,{\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (t \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 8 \,{\mathrm e}^{4 t}+t
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {t}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y-1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{3}-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (t^{2}+1\right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y+{\mathrm e}^{-3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y+{\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t -y
\] |
✓ |
✓ |
|
\[
{}t y^{\prime }+2 y = \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \tan \left (t \right ) y+\sec \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 t y}{t^{2}+1}+t +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \tan \left (t \right ) y+\sec \left (t \right )^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y
\] |
✓ |
✓ |
|
\[
{}t y^{\prime } = y+t^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\tan \left (t \right ) y+\sec \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y}{t +1}
\] |
✓ |
✓ |
|
\[
{}t y^{\prime } = -y+t^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 \tan \left (2 t \right ) y = \tan \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}t \ln \left (t \right ) y^{\prime } = t \ln \left (t \right )-y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y}{-t^{2}+1}+3
\] |
✓ |
✓ |
|